2003
DOI: 10.1038/sj.bjc.6600725
|View full text |Cite
|
Sign up to set email alerts
|

Randomised phase III trial of irinotecan combined with cisplatin for advanced non-small-cell lung cancer

Abstract: To determine a standard combination chemotherapy for patients with advanced non-small-cell lung cancer (NSCLC), we conducted a phase III trial of irinotecan (CPT-11) to test the hypotheses that CPT-11+cisplatin is superior to cisplatin+vindesine and that CPT-11 monotherapy is not inferior to cisplatin+vindesine. A total of 398 patients with previously untreated NSCLC were randomised to receive cisplatin+CPT-11 (CPT-P), cisplatin+vindesine (VDS-P) or CPT-11 alone (CPT). In the CPT-P arm, CPT-11 60 mg m À2 was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
109
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 25 publications
0
109
1
Order By: Relevance
“…Two other single agents were recently investigated in a secondline setting in NSCLC patients. Gefitinib, an orally active EGFR tyrosine kinase inhibitor, was studied in a randomised phase II trial (Fukuoka et al, 2003). Antitumour activity, with a response rate between 18 and 19%, as well as symptom relief and improvement in quality of life was reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two other single agents were recently investigated in a secondline setting in NSCLC patients. Gefitinib, an orally active EGFR tyrosine kinase inhibitor, was studied in a randomised phase II trial (Fukuoka et al, 2003). Antitumour activity, with a response rate between 18 and 19%, as well as symptom relief and improvement in quality of life was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with platinum-based chemotherapy improves survival and quality of life in patients with advanced non-small-cell lung cancer (NSCLC) (Souquet et al, 1993; Non-small Cell Lung Cancer Collaborative Group, 1995; Cullen et al, 1999;Anderson et al, 2000;Ranson et al, 2000;Schiller et al, 2002). Since two trials demonstrated clinically beneficial effects of docetaxel in second-line setting (Fossella et al, 2000;Shepherd et al, 2000), docetaxel 75 mg m À2 is currently considered the standard regimen to which other experimental schedules should be compared.Irinotecan, a semisynthetic water-soluble analogue of camptothecin, has shown activity in NSCLC patients as single agent and in combination with docetaxel (Fukuoka et al, 1992; Adjei et al, 2000;Masuda et al, 2000;Satouchi et al, 2001;Negoro et al, 2003). Moreover, Irinotecan demonstrated activity as single agent in pretreated patients (Sanchez et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of irinotecan for gastrointestinal cancers is more or less empirical and use within clinical trials for other malignant tumours may show equal effectiveness. Existing data combining irinotecan with other agents such as cisplatin (Cardenal et al, 2003) show an effectiveness comparable to other established treatments in NSCLC (Negoro et al, 2003). For the present study, the second agent selected for combination treatment with irinotecan was paclitaxel, which has been tested as first-line combined treatment for advanced NSCLC (Chang et al, 1996;Greco and Hainsworth, 1997;Belani et al, 1999;Bonomi et al, 2000;Stathopoulos et al, 2004).…”
mentioning
confidence: 93%
“…This biweekly (every 2 weeks) chemotherapy schedule was based on recent trials with proper dosage adjustment and a successful outcome (Cardenal et al, 2003;Negoro et al, 2003). Our objectives were to determine response rate, toxicity, and median and overall survival.…”
mentioning
confidence: 99%